2022
DOI: 10.1002/hsr2.567
|View full text |Cite
|
Sign up to set email alerts
|

Normative data for three physical frailty parameters in an aging, rural Indian population

Abstract: Introduction Physical frailty is associated with multiple adverse health outcomes. Since physical characteristics markedly vary with different populations, population‐specific norms for physical frailty parameters are necessary. Such norms are lacking for the Indian population, especially for older, rural Indians. We aimed to develop normative values for three quantitative, frailty parameters—handgrip strength, “Timed Up‐and‐Go” (TUG) test time, and physical activity in an aging, rural Indian population. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 50 publications
1
2
0
Order By: Relevance
“…Possible explanations for female preponderance in cognitive impairment in our rural cohort could be due to the lower levels of literacy, higher prevalence of nutritional deficiencies, and higher rate of early life socio‐economic disadvantages in rural women as compared to their male counterparts. Furthermore, in our rural cohort, we have also observed a significantly higher prevalence of physical frailty 48 in women than men. In the urban cohort, higher prevalence in male as compared to female subjects could be due to a higher prevalence of vascular risk factors, particularly hypertension, in Indian male as compared to female subjects, as demonstrated by a recently‐published study based on data from the National Family Health Survey‐4 in India 49 .…”
Section: Discussionsupporting
confidence: 67%
“…Possible explanations for female preponderance in cognitive impairment in our rural cohort could be due to the lower levels of literacy, higher prevalence of nutritional deficiencies, and higher rate of early life socio‐economic disadvantages in rural women as compared to their male counterparts. Furthermore, in our rural cohort, we have also observed a significantly higher prevalence of physical frailty 48 in women than men. In the urban cohort, higher prevalence in male as compared to female subjects could be due to a higher prevalence of vascular risk factors, particularly hypertension, in Indian male as compared to female subjects, as demonstrated by a recently‐published study based on data from the National Family Health Survey‐4 in India 49 .…”
Section: Discussionsupporting
confidence: 67%
“…This article contributes to the existing literature ( 49 , 50 ) on the heterogeneity of frailty trajectories by estimating reference curves that account for the longitudinal nature of frailty, showing heterogeneity in the association of sex and education for different levels of frailty, and considering the missing data and death processes to reduce bias in inferences. Furthermore, our results supplement recent work on the consistency and reliability of the FI to target policies among groups of community-dwelling older adults ( 51 ).…”
Section: Discussionmentioning
confidence: 99%
“…In our study, it is also shown that grip strength showed the best sensitivity and accuracy for the male participants than the other frailty components. Generally, grip strength becomes weaker with age, eventually affecting older adults’ quality of life [ 29 , 30 ]. However, older males are more vulnerable because of dynapenia [ 31 , 32 ], as they exhibit more age-related loss of muscle strength [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%